Foreign Direct Investments and Internal Migration in China’s Special Economic Zones from 1990 to 2020 : A Comparative Study of Shenzhen and Shantou - Wang, Letian; Růžičková, Barbora; Kotrba, Vojtěch; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis investigates the dynamic relationship between foreign direct investment (FDI) and internal migration in two of China’s earliest Special Economic Zones, Shenzhen and Shantou, from 1990 to 2020. Using annual city-level data and vector autoregression (VAR) models, the study analyzes how shocks to FDI, GDP per capita, GDP growth, employment, and industrial structure influence population growth in each city. The results reveal sharply contrasting migration regimes. In Shenzhen, population growth displays limited persistence and only weak responses to investment and macroeconomic shocks, reflecting a mature, diversified urban economy where migration is shaped primarily by overall labor-market conditions. In Shantou, population growth is more volatile and remains sensitive to FDI shocks and structural factors, indicating a heightened responsiveness to external signals despite the limited scale of these effects, reflecting incomplete industrial upgrading. These findings highlight that the impact of FDI on migration is highly conditional on local institutional capacity and structural transformation. The thesis contributes to the literature by providing a long-run comparative analysis of two SEZs with shared origins but divergent outcomes and by demonstrating how dynamic time-series methods can illuminate the mechanisms linking investment and labor mobility.
Vedoucí práce: Barbora Růžičková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses